PENGARUH KEBIJAKAN KURIKULUM MERDEKA PADA MINAT BACA SISWA DI SDN PEMURUS DALAM 6 BANJARMASIN - Annisa Meilida; Nor lila Sari (Cangkal : Jurnal Ilmu Sosial Dan Humaniora, 2025)
The purpose of this study was to determine the effect of the independent curriculum policy on the reading interest of students at SDN Pemurus Dalam 6 Banjarmasin. The research sample consisted of 65 students from grade III and grade V. The research location was SDN Pemurus Dalam 6 Banjarmasin. This study used a correlational research method. The results of the T-test (partial test) obtained a t-value of 1.931> t-table 1.990 so it can be concluded that the independent curriculum variable (X) has an effect on students' reading interest (Y). Based on the significance value obtained of 0.006. This shows that the significance value of 0.006 <0.05 so it can be concluded that H0 is rejected and H1 is accepted. Meanwhile, based on the results of the coefficient of determination test, it was found that the influence of the independent curriculum policy (X) on students' reading interest (Y) where the Adjusted R square value was 0.256, which means the influence of the independent curriculum policy (X) on students' reading interest (Y) was 25.6% so that there was 74.4% influenced by other factors that were not the focus of the study